Feasibility study of renewable energy installations in Pulau Tioman using levelized cost of energy - Nur Adriana Hasya binti Mohd Azhar (2023)
That thesis reported about the case studies on status of electrical supply and ongoing RE projects in Pualau Tioman. There will be three feasibility studies under the case studies on status of electrical supply which are Electric Generation and Load Profile and Design a Power System Protection Scheme at SJL Tekek.